2016
DOI: 10.1080/10715762.2016.1189546
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide promotes gastric wound healing in mice via the protein kinase C pathway

Abstract: Previous studies have shown that carbon monoxide (CO) is involved in a variety of physiological and pathophysiological processes including anti-inflammatory, anti-apoptotic and anti-oxidant responses. However, it remains unclear whether CO promotes gastric ulcer healing. In the present study, we evaluated the efficacy of CO-saturated saline in the treatment of gastric ulcers and its underlying mechanism. Acute gastric ulcers were induced in C57BL/6 male mice using acetic acid. A CO-saturated solution was prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Similar anti‐inflammatory activities of CO have also been established in mice models of experimental autoimmune encephalomyelitis and experimental cerebral malaria, which might imply that CO has the potential to prevent neuroinflammation in humans . Moreover, CO has been recognized as a potential new treatment for inflammatory disorders of the digestive system such as postoperative ileus, inflammatory bowel disease, gastric ulcers, diabetic gastroparesis, and acute liver injury . Another important field of anti‐inflammatory therapy using CO is sepsis.…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 82%
“…Similar anti‐inflammatory activities of CO have also been established in mice models of experimental autoimmune encephalomyelitis and experimental cerebral malaria, which might imply that CO has the potential to prevent neuroinflammation in humans . Moreover, CO has been recognized as a potential new treatment for inflammatory disorders of the digestive system such as postoperative ileus, inflammatory bowel disease, gastric ulcers, diabetic gastroparesis, and acute liver injury . Another important field of anti‐inflammatory therapy using CO is sepsis.…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 82%
“…Interestingly, CO produced endogenously or released from its pharmacological donors, including tricarbonyldichlororuthenium (II) dimer (CORM-2), has been demonstrated to protect the gastric mucosa against the damage induced by exposure to systemic stress or the administration of ethanol, alendronate or aspirin (ASA) (Gomes et al, 2010;Magierowska et al, 2015Magierowska et al, , 2016Magierowski et al, 2016a,b;Kwiecien et al, 2016). Interestingly, COsaturated saline promotes gastric ulcer healing, but the mechanism of this beneficial effect on ulcer healing has been little studied (Takagi et al, 2016). In particular, the involvement of CO-releasing CORM-2 in the healing of preexisting gastric ulcers has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…New evidence suggests that HMOX-1 is not directly involved in anti-oxidative stress and other reactions, but by up-regulating CO to protect 50. In terms of its role in gastric mucosa, CO exhibits its anti-inflammatory, anti-apoptotic and anti-oxidant responses in many ways 51. A large number of studies have found that the three of them interact with each other 5253.…”
Section: Mechanisms Of Hydrogen Sulfide In Gastric Mucosa Damage Antimentioning
confidence: 99%